Epidemiological Analysis of Glomus Tumors of the Hand and Association with Recurrence Rate - Guedes, Giovanni Vilardo Cerqueira; Jácome, Daniel Torres; Alves, Gabriel Farias; Monteiro, Anderson Vieira (Revista Iberoamericana de Cirugía de la Mano, 2022)
Introduction Glomus tumors are benign, characterized by microvascular alteration, and mostly found in the subungual region of the hand. They are rare and associated with paroxysmal pain, tenderness on palpation, and thermal sensitivity. The aim of the present research was to analyze the epidemiology of glomus tumors and relate each of the variables with cases of recurrence.Materials and Methods A retrospective review of medical records was undertaken in our hospital to collect epidemiological numerical variables (time between the onset of symptoms and diagnosis and surgery, age, size of the tumor on magnetic resonance imaging and the histopathological examination, time until recurrence and reoperation after surgery, duration of the follow-up) and categorical variables (gender, ethnicity, laterality, affected finger, location in the hand, surgical technique, smoking, preoperative symptoms, recurrence, and comorbidities). Then, we performed a statistical analysis to identify possible associations of the hand tumors with recurrences.Results The review identified 66 patients with glomus tumors 52 of which were located in the hand. The mean age of the sample was 49 years, and it was mostly composed of white female patients. Pain was the main related symptom, and most tumors presented sizes between 5 mm and 1 cm. Among the 52 patients, 11 cases presented recurrences, with a mean time until onset of 39.4 months, but 3 of them were initially operated on at other hospitals. None of the variables was shown to be a predictor of recurrence, although we saw that bone involvement on radiographs was only present in certain cases of recurrence.Conclusion The sample studied was large for this rare disease, and reinforced previous results regarding its epidemiology. As 54% of the cases of recurrence occurred at least twice, we think that genetic, histological and immunohistochemical analyses should be the focus of futures studies, as well as a search for bone and tendon involvement.
Keywords: epidemiology; glomus tumor; hand